PREVALENCE OF MECHANICAL VS. NON-MECHANICAL COMPLICATIONS IN PATIENTS WITH ACUTE STEMI - Owais Shams1, Nandlal Rathi2, Jagdesh Kumar3, Abdul Aziz Sahito4, Kartik Kumar Rathi5 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
OBJECTIVE: The aim behind this study was to scientifically determine the prevalence of mechanical vs. non-mechanical complications in patients with acute STEMI. PATIENTS AND METHODS: A prospective observational study has been conducted in the department of cardiology Isra University Hospital Hyderabad through a convenience sampling technique on all patients presented and admitted with acute STEMI after taking written and informed consent. Patients were evaluated for non-mechanical and mechanical complication during 48 hours after admission. Data were entered and analyzed by using Statistical Package for the Social Sciences version 19.0. RESULTS: The mean age of patients was 52.56 years (14.39 ± SD) and the study subjects consisted of 43 males (70%) and 18 (30%) females. Out of 61 patients majority of the patients were presented between the ages of 51 – 65 years (N = 22.25%). The overall prevalence of non-mechanical and mechanical complications was 10 (16.39%) and 24 (39.34%), respectively. The most common non-mechanical complication was development of arrhythmias 8 (80%) and the most common mechanical complication was development of left ventricular failure 12 (33.33%), respectively. CONCLUSION: The present findings indicate that most of the STEMI patients were belongs to middle aged population and among them mechanical complications were more prevalent than non-mechanical complications.